2005
DOI: 10.1007/s11199-005-5679-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fathers' Absence on African American Adolescents' Gender Role Development

Abstract: Gender role development was assessed in 52 father-absent and 54 father-present African American adolescents. Father-present boys, especially those from lower-income backgrounds, had higher perceptions of their masculinity than did father-absent boys. Lower income father-absent girls perceived themselves to be higher in masculinity than did all other girls. Consequently, father-present adolescents tended to have more traditional gender role orientations than did those in father-absent homes. It is argued that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 63 publications
3
67
0
6
Order By: Relevance
“…[33][34][35] Higher levels of agreement with traditional masculinity beliefs are generally associated with risk behaviors such as sexual partner concurrency and inconsistent condom use. [36][37][38] Some researchers have suggested that growing up with non-resident fathers is associated with less adherence to traditional masculinity norms, 39 which might be interpreted as portending lower sexual risk. On the other hand, other work in adult black MSM described lack of masculine socialization from absent biological fathers in childhood and adolescence as a potentially detrimental influence on partner selection and risky sex later in life.…”
Section: Masculine Socializationmentioning
confidence: 99%
“…[33][34][35] Higher levels of agreement with traditional masculinity beliefs are generally associated with risk behaviors such as sexual partner concurrency and inconsistent condom use. [36][37][38] Some researchers have suggested that growing up with non-resident fathers is associated with less adherence to traditional masculinity norms, 39 which might be interpreted as portending lower sexual risk. On the other hand, other work in adult black MSM described lack of masculine socialization from absent biological fathers in childhood and adolescence as a potentially detrimental influence on partner selection and risky sex later in life.…”
Section: Masculine Socializationmentioning
confidence: 99%
“…It may be speculated that androgynous gender roles are associated with better HRQOL among African-American girls because demonstrating leadership and autonomy can be helpful when confronted with challenges more common in their experience, such being raised by a single parent where supervision and support may be less available [32]. White girls, both nationally and within this sample, are more likely to come from higher SES households in which having orientations toward caring and empathy may be more normative and do not generally result in pressures to neglect their own health [25].…”
Section: Discussionmentioning
confidence: 99%
“…As gevolg daarvan is dit vir 'n groot aantal vaders nie moontlik om saam met hulle kinders te leef en om hulle te onderhou nie (Holborn & Eddy, 2011;Madhavan, Townsend, & Garey, 2008;Smit, 2004;Steyn, 1993). Mandara, Murray, and Joyner (2005) voer aan dat die nalatenskap van apartheid, werkloosheid, armoede en ongelykheid in postapartheid Suid-Afrika, geslagsongelykheid en MIV/VIGS, 'n nadelige impak het op gesinspraktyke en die betrokkenheid van vaders by hul kinders se lewens.…”
Section: Agtergrondunclassified
“…In 'n studie wat gedoen is deur Mandara et al (2005), is bevind dat vaderlose dogters van 'n lae-inkomstegroep, h e a l t h s a g e s o n d h e i d 2 0 ( 2 0 1 5 ) 4 5 e5 8 hulleself as meer manlik beskou as dogters met betrokke vaders. Hulle is meer geneig om eienskappe soos onafhanklikheid en selfgelding te ontwikkel vanwe€ e die feit dat hulle nie gewoond is aan 'n beskermende vaderfiguur wat hulle in tye van nood bystaan nie (Cruz et al 2011;Green, 1976:72;Goodsell & Meldrum, 2010).…”
Section: Probleemstellingunclassified
See 1 more Smart Citation